Quo Vadis Nikah Sirri Perspektif Hukum Islam - Nawawi Nawawi (Hukum Keluarga Islam IAIN LANGSA, 2020)
Islam requires marriage which is a sacred bond in human life. Through a legal marriage, human relationships of different types are lawful and become observance. The household life is built in an atmosphere of peaceful peace and affection between husband and wife and their descendants. The purpose of this article is to find out: The pillars and conditions of marriage according to Islam, the factors that cause sirri marriages, and the consequences of sirri marriages on their families. The method used in this study is a research library. Meanwhile, descriptive is describing the existence of a theme to be presented. Then by collecting relevant and accurate books or references, reading also studying to obtain data or conclusions related to the discussion. Sirri marriage in the perspective of Islamic law is valid until it meets the pillars and conditions of marriage. The contributing factors include: lack of knowledge about the importance of marriage registration, economy, difficulty in obtaining polygamy and social permits in some communities, on the grounds of maintaining honor and religion.